Pathogenicity and infectivity of the Thai-strain densovirus (AThDNV) in Anopheles minimus s.l. - R. Theophil Rwegoshora (2018)
We report the first experimental infection of an anopheline, An. minimus s.l., with the Thaistrain densovirus, AThDNV. Two hundred first-instar larvae were raised in 2 virus concentrations; mortality in the low virus concentration was no different than that in controls (9.5% vs 7.5%, respectively). Mortality in the high virus concentraion was 17.5%. Among surviving adults, infection rates were 33.3% (low concentration) and 15.5% (high concentration), as judged by PCR-screening. Infection rates did not differ between males and females. All orally-infected females transmitted densovirus to at least some of their offspring. Vertical transmission rates ranged from 25.0-53.8%. Densovirus infection did not appear to affect fecundity, either in the number of eggs laid or the number of eggs hatched.